The association between clinical, subclinical features and autoantibody profile in Vietnamese dermatomyositis patients. - My Huyen Le; Hoa Thi Dinh; Thu Thi Hoai Le; Phuong Thi Hoang; Minh Nguyet Vu; Doanh Huu Le (Public Library of Science (PLoS), 2023)
There is still a lack of research in Vietnam on the autoantibody profile of dermatomyositis (DM) and its association with clinical and subclinical characteristics. Therefore, we conducted this study to investigate clinical and subclinical correlations with autoantibodies in DM patients. 72 DM patients at Vietnam National Hospital of Dermatology and Venereology (NHDV) from March 2019 to September 2021 were included in this cross-sectional study. Clinical manifestations and laboratory test results of the patients were obtained at the time of visit. Of these, 63 patients were tested for the presence of autoantibodies using an Immunoblot assay. Our findings show that the average age of patients was 41.7 years. The female-male ratio was 1.7:1. The most common skin and muscle manifestations were myalgia (79.2%), heliotrope rash (62.5%), shawl sign (61.1%), Gottron's sign (59.7%), muscle weakness (59.7%), Gottron's papule (52.8%), periungual telangiectasia (41.7%), V-sign (38.9%), poikiloderma (26.4%), periungual fissures (20.8%), Raynaud's phenomenon (15.3%). Among the 63 patients tested for autoantibodies, myositis-specific antibodies (MSAs) were found in 71.4% of the serum samples, and myositis-associated antibodies (MAAs) in 36.5%. Anti-TIF1γ antibody accounted for the highest percentage (28.6%), followed by anti-Ro52 (22.2%), anti-synthetase (17.5%), anti-Mi-2 and anti-MDA5 (both 14.3%). Anti-synthetase antibodies (ARS-Abs) showed a significant association with arthralgia, fever, and Raynaud's phenomenon, while anti-TIF1γ antibodies showed a strong association with V-sign and poikiloderma (p<0.05). Clinical features in dermatomyositis are heterogeneous. Our study results show some associations between clinical features and autoantibodies in patients with DM. The analysis of DM-related autoantibodies is clinically useful, will be essential for the approaches to diagnosis, and management of DM patients.